2013
DOI: 10.1111/bjhp.12048
|View full text |Cite
|
Sign up to set email alerts
|

Understanding donation experiences of unspecified (altruistic) kidney donors

Abstract: What is already known on this subject? Unspecified living kidney donation is an under-researched area with only three research papers published worldwide that report on the motivations and experiences of donors. These studies indicate that donors endorse pro-social values and receive positive interpersonal and intrapersonal benefits from donation. What does this study add? UKDs' experiences are made explicit and provide a framework for future research. Social connections (capital) are an important precursor to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
75
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(81 citation statements)
references
References 52 publications
6
75
0
Order By: Relevance
“…The compelling nature of organ donation for participants in this study has also been found in existing research with directed kidney donors (Clarke et al, 2013;Franklin and Crombie, 2003;Gill and Lowes, 2008;Lennerling et al, 2003). The current research goes further in addressing the way that altruistic donors use ideas about emotions and rationality in their discursive repertoires, suggesting the possible subjective experience that each allows for.…”
Section: Health 0(0)supporting
confidence: 68%
See 2 more Smart Citations
“…The compelling nature of organ donation for participants in this study has also been found in existing research with directed kidney donors (Clarke et al, 2013;Franklin and Crombie, 2003;Gill and Lowes, 2008;Lennerling et al, 2003). The current research goes further in addressing the way that altruistic donors use ideas about emotions and rationality in their discursive repertoires, suggesting the possible subjective experience that each allows for.…”
Section: Health 0(0)supporting
confidence: 68%
“…This binary construction of altruistic donors as heroes or as potentially 'mad' reduces opportunities for a more useful understanding of what leads people to want to be altruistic donors. The reduction of the donor's motives to being either 'mad' or 'brave' has also been found by Clarke et al, (2013). There are important implications for assessment, regulation and practice.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…In-depth qualitative analysis has shown “discouraging donation” produces interpersonal stress and emotional distress due to conflict with social ties. 23,31 It is possible that social conflict due to disagreement about donation could lead to emotional distress that is expressed in response to pain.…”
Section: Discussionmentioning
confidence: 99%
“…31 Non-directed altruistic donors, much like directed donors, report being motivated by a desire to benefit other people or society as a whole, a compelling desire to donate and recognise personal psychosocial gains. [32][33][34] Where commercial organ trading exists, or where donation is financially incentivised, most unrelated donors report financial motivation. [35][36][37][38] Payment for donation is illegal in almost all countries.…”
mentioning
confidence: 99%